2018
DOI: 10.3390/rs10071155
|View full text |Cite
|
Sign up to set email alerts
|

TerraSAR-X Time Series Fill a Gap in Spaceborne Snowmelt Monitoring of Small Arctic Catchments—A Case Study on Qikiqtaruk (Herschel Island), Canada

Abstract: Abstract:The timing of snowmelt is an important turning point in the seasonal cycle of small Arctic catchments. The TerraSAR-X (TSX) satellite mission is a synthetic aperture radar system (SAR) with high potential to measure the high spatiotemporal variability of snow cover extent (SCE) and fractional snow cover (FSC) on the small catchment scale. We investigate the performance of multi-polarized and multi-pass TSX X-Band SAR data in monitoring SCE and FSC in small Arctic tundra catchments of Qikiqtaruk (Hersc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 78 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Wet snow is typically identified using change detection applied to the backscatter ratio between an image with wet snow and a reference image with only dry snow or no snow. A constant threshold of -2 dB or -3 dB is often used to generate a wet snow mask [9,11,13,14]. Soft thresholds, as a function of the backscatter ratio, have been used to derive the probability of wet snow [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Wet snow is typically identified using change detection applied to the backscatter ratio between an image with wet snow and a reference image with only dry snow or no snow. A constant threshold of -2 dB or -3 dB is often used to generate a wet snow mask [9,11,13,14]. Soft thresholds, as a function of the backscatter ratio, have been used to derive the probability of wet snow [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…for each vegetation class as well as the confidence interval (95%). The period with presence of snow was set between mid-September and mid-May based on prior observations (Burn and Zhang, 2009;Stettner et al, 2018). Figure 5c shows the monthly average temperature and cumulative monthly precipitation on Qikiqtaruk-Herschel Island.…”
Section: Spatial and Temporal Evolution Of Cpdmentioning
confidence: 99%
“…Like open water, wet snow is characterized by low backscatter. Wet snow typically absorbs the microwave signal and reduces the backscatter intensity significantly (further TerraSAR-X examples in similar settings: Antonova et al, 2016;Mora et al, 2017;Stettner et al, 2018), which caused the false classification result.…”
Section: Sar Capabilities For Separation Of Relevant Landcover Typesmentioning
confidence: 99%
“…They found that the separability between sand and water backscatter in Cband strongly depends on the incidence angle and polarization. Differences in applicability of certain wavelengths are also to be expected due to their varying sensitivity to waves on the water and surface roughness (modified by vegetation and snow; examples from Arctic sites in Stettner et al, 2018;Bartsch et al, 2020) on land, which leads to ambiguities. Wet snow appears similar to water (low backscatter), as do radar shadow areas.…”
Section: Introductionmentioning
confidence: 99%